Organisational Commitment and Extra-Role Behaviour: A Survey in Iran’s Insurance Industry - Davoudi , Seyed Mehdi Mousavi (Journal of Law and Governance, 2012)
The present study was conducted in Babol, a city in north of Iran, and aimed to analyze the relationships among Organizational Commitment (OC) components and employees’ extra-role behavior which is known as Organizational Citizenship Behavior (OCB). We choose Affective commitment (AC), Normative Commitment (NC), and Continuance Commitment (CC) as the three components of OC; and the analysis was carried out utilizing Structural Equation Modeling (SEM) methodology by LISREL 8.8 software. There were 300 employees in 47 branches of “Iran Insurance”. According to Krejcie and Morgan (1970), the minimum number of sample size was determined as 169 employees. A total of 275 questionnaires were distributed among the employees and 190 usable questionnaires were returned. The factors analysis and the findings show that AC and NC have a significant positive influence on OCB. This finding implied that the higher the level of AC and NC, tended to increase the level of employees’ OCB. Further, no significant relationship was found between CC and OCB.